WAYS TO FURTHER IMPROVE THE ACTIVITY OF COTTON-TEXTILE CLUSTER (Marketing Journal, 2025)
This article presents a scientific and theoretical analysis of the economic significance of clustering in the cotton textile sector, its role in increasing production efficiency and its impact on the formation of the value chain. The study highlights the potential for efficient resource use, reduced production costs, and increased volumes of competitive products by organizing all stages, from cotton cultivation to finished textile production, into a single system.
Keywords: cluster; cotton yield; textile clusters; trend; textile products; competitive products; clustering